Preparation of Rat Whole-kidney Acellular Matrix via Peristaltic Pump - Liu, Rongfu; Gao, Jiasheng; Yang, Yufeng; Zeng, Weixin (Urology Journal, 2015)
Purpose: To design a whole-kidney a cellular matrix scaffold using peristaltic pump perfusion and to ascertain the retention of extra cellular proteins by the scaffold. Materials and Methods: Male Sprague-Dawley (SD) rats weighing 200-250 g were used. Intravenous catheters were inserted into the renal artery followed by perfusion of decellularization solution using a peristaltic pump. After decellularization, the acellular matrix was observed under a microscope after hematoxylin and eosin (H&E) staining and a fluorescence microscope after 4′,6-diamidino-2-phenylindole (DAPI) staining. Immunohistochemistry was used to identify the composition of kidney acellular matrix. Results: The result of H&E and DAPI staining demonstrate the removal of cellular material in kidney a cellular matrix. Immunohistochemistry confirmed the conservation of the natural expression of extra cellular matrix proteins including collagen types I and IV, fibrin and laminin. Conclusion: Peristaltic pump perfusion enables successful preparation of renal a cellular matrix, to retainthe criticalproteins of natural extra cellular matrix. The resulting kidney a cellular matrix represents an ideal natural scaffold for renal tissue engineering.